Electrical double-layer capacitors with plasticized polymer electrolyte based on methyl cellulose - Shuhaimi, N.E.A.; Teo, L.P.; Woo, H.J.; Majid, Siti Rohana; Arof, Abdul Kariem (Springer Verlag (Germany), 2012)
Poly(ethylene glycol) plasticized polymer electrolytes based on methyl cellulose have been prepared using the solution casting technique. Interactions between component materials in the electrolyte have been examined using Fourier transform infrared spectroscopy. The polymer-salt spectrum indicates that interaction occurred at the oxygen atom with the shift of the C-O stretching mode. Inference from the Nyquist plot suggests that the material can be represented by a resistor connected in series with a constant phase element. Capacitance evaluated from the fitting equation representing impedance of the equivalent circuit is observed to decrease with increasing temperature. From linear sweep voltammogram, the 63.75 wt% MC-21.25 wt% NH4NO3-15 wt% PEG, which is the highest conducting plasticized sample shows good electrochemical stability. This material has been tested as an electrolyte in electrical double-layer capacitor fabricated in this study. The electrochemical properties of the capacitors have been investigated by cyclic voltammetry, charge-discharge, and self-discharge characteristics. The discharge capacitance obtained is 38 F g(-1).